Collaboration in marketing regional tourism destinations: Constructing a business cluster formation framework through participatory action research. (March 2021) - Perkins, Rachel; Khoo-Lattimore, Catheryn; Arcodia, Charles
Abstract: Current research advocates for the effectiveness of tourism business clusters in promoting collaboration between stakeholders and successfully marketing destinations. However, there is a lack of insight on how a cluster is actually formed in order to reap such benefits, if a cluster does not already pre-exist within a region. Importantly, there is no research framework to explain the steps involved in forming a tourism business cluster in these areas. This inhibits regions that don't have an operational cluster in gaining the benefits of this form of collaboration. The purpose of this paper is to demonstrate how tourism businesses progress through the phases of cluster formation, enabling them to contribute to destination branding for their region. This paper presents the phases and their inherent steps to forming a tourism business cluster resulting from a Participatory Action Research (PAR) study where stakeholders formed a tourism business cluster in a regional destination in Queensland, Australia. The study involved participants from local tourism businesses, the local council, the local tourism organisation, regional tourism organisation, and state tourism organisation. Findings reveal three distinct phases to cluster formation, with each phase encompassing multiple steps. The newly formed cluster enabled participants to contribute to their region's destination brand through the creation of an event for their region. This study contributes important insights to the bodies of literature on collaboration and business clustering, as well as managerial implications for enhancing collaboration structures in a region. Highlights: The business cluster formation process involves an important 'pre-cluster' formation and 'cluster development' stage. The cluster formation and development stages occur in a cyclic process. Cluster members call for tangible activities to enable them to work towards destination branding activities. Cluster members experienced opportunities in networking with other likeminded people.